Developing an Effective Digital Marketing Strategy with a Perceptual Mapping Approach Using the Multidimensional Scaling (MDS) Method (Case Study on Local Fashion Brands in Batam City) - Makaba, Kharisma Austin; Ayunintyas, Ni Putu Winda; Penny, Penny (SEIKO : Journal of Management & Business, 2024)
The rapid development of technology has intensified business competition. Thus, innovation is a key path for businesses to survive and thrive in the current era of digitalization. The urgency of this research is to assist various local fashion brands in Batam City in developing effective digital marketing strategies to increase brand awareness and competitiveness in a market still dominated by export products. This research aims to provide an overview of consumer perceptions of the digital marketing efforts made by three local fashion brands in Batam City, as well as to understand what types of digital marketing strategies consumers prefer and desire. The research also aims to formulate effective digital marketing strategies for local fashion brands in Batam City. In other words, this research seeks to propose digital marketing strategies. The methods used in this study consisted of mapping consumer perceptions using Multidimensional Scaling (MDS), SWOT analysis, and in-depth interviews. The results of this research indicated that the local fashion brand NHB excels in SEO, Content Marketing, and Influencer Marketing; AFI excels in PPC; and DSY is perceived differently and is not closely associated with any specific marketing attributes. The proposed marketing strategy for local fashion brands in Batam City is to maximize the use of social media platforms with engaging content, such as mix-and-match tutorials and funny videos, collaborate with local influencers, and make products easily discoverable through search engines and various other sites.